“Não existe branquitude”: um estudo sobre a articulação entre os conceitos de branquitude e negação - Freitas, Ivo Gabriel Belucci de (Universidade Federal de São Carlos, 2025)
Whiteness, defined as a structure of power and white racial identity, relates to the psychoanalytic concept of denial, as a defense mechanism that, according to Freud, allows the emergence of unconscious contents under the condition of being denied. In Brazil, Lélia Gonzalez points to denial as the basis of structural racism, highlighting how Brazilian culture erases the African contribution and reinforces the universality of whiteness. Therefore, this work aims to investigate the relationship between the concepts of denial, drawing on theoretical contributions from psychoanalysis and sociology, in order to understand how the defense mechanism of denial, through the suspension of repression, contributes to the construction of white racial identity and the maintenance of its privileges in Brazilian society. To this end, an analysis of psychoanalytic and sociological works will be carried out, following Garcia-Roza's (1991) model of theoretical psychoanalytic research.
"There is no such thing as whiteness": a study on the articulation between the concepts of whiteness and negation
Keywords: Branquitude; Negação; Privilégios; Racismo; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO; 10. Redução das Desigualdades